Reflections of Homeless Women and Women with Mental Health Challenges on Breast and Cervical Cancer Screening Decisions: Power, Trust, and Communication with Care Providers - Moravac, Catherine Claire (Frontiers in Public Health, 2018)
This study conducted in Toronto, Canada explored the perceptions of women living in homeless shelters and women with severe mental health challenges about the factors influencing their decision-making processes regarding breast and cervical cancer screening. Twenty-six in-depth qualitative interviews were conducted. The objectives of this research were: (i) to provide new insights about women’s decision-making processes, (ii) to describe the barriers to and facilitators for breast and cervical cancer screening, and (iii) to offer recommendations for future outreach, education and screening initiatives developed specifically for under/never-screened marginalized women living in urban centres. This exploratory study utilized thematic analysis to broaden our understanding about women’s decision-making processes. A constructed ontology1 was used in an attempt to understand and describe participants’ constructed realities. The epistemological framework was subjective and reflected co-created knowledge. The approach was hegemonic, values-based and context-specific. The aim of the analysis was to focus on meanings and actions with a broader view to identify the interplay between participants’ narratives and social structures, medical praxis and policy implications. Results from 26 qualitative interviews conducted in 2013-14 provided insights on both positive and negative prior cancer screening experiences, the role of power and trust in women’s decision-making, and areas for improvement in health care provider/patient interactions. Outcomes of this investigation contribute to the future development of appropriately designed intervention programs for marginalized women, as well as for sensitivity training for health care providers. Tailored and effective health promotion strategies leading to life-long cancer screening behaviours among marginalized women may improve clinical outcomes, decrease treatment costs and save lives. 1Ontology refers to the study of the nature of being. It explores the nature and form of social reality and from that what can be known. Key Words: Homeless, Mental Health, Cancer Screening, Mammogram, Papanicolaou, Qualitative